The influence of caregiver preparedness, perceived social support and general self-efficacy on self-contribution among stroke caregivers: a cross-sectional study - Teng, Hui; Tan, Zhou; Zhen, Mengni; Shu, Qingxia (Frontiers in Public Health, 2025)
BackgroundCaregivers’ self-care contributions are crucial for enhancing stroke patients’ self-care capabilities, and patients receiving family support often demonstrate higher treatment adherence. Although it is widely recognized that caregivers’ preparedness to provide care positively influences self-care contributions, the underlying mechanisms of this association remain unclear. This study aims to explore the mechanisms through which caregiver preparedness, perceived social support, and general self-efficacy influence caregiver readiness and self-care contribution among stroke caregivers in the contemporary Chinese context.AimBased on the Individual and Family Self-Management Theory (IFSMT) model, this study examined the effects of caregivers’ caregiving preparedness, perceived social support, and general self-efficacy on their self-care contribution among stroke caregivers.DesignA cross-sectional study.MethodsUsing convenience sampling, 277 stroke caregivers from four tertiary Grade A hospitals in Xiangxi, Hunan Province, China were surveyed with paper-based questionnaires during outpatient follow-up visits in July 2024. Data were analyzed using SPSS/AMOS for descriptive statistics, Pearson correlation, multiple regression, and structural equation modeling with bootstrapping to test hypothesized relationships and mediation effects.ResultsThe self-care contribution was at a moderate level, showing significant positive correlations with caregiving preparedness, perceived social support, and general self-efficacy. Both perceived social support and general self-efficacy demonstrated partial mediating effects between caregiving preparedness and self-care contribution.ConclusionImproving caregivers’ self-care contribution requires focused attention on enhancing caregiving preparedness, perceived social support, and general self-efficacy. The study highlights the bridging role of perceived social support and general self-efficacy between preparedness and contribution. Clinical interventions should: ① strengthen preparedness through standardized training, ② build social support networks for psychological empowerment, and ③ employ motivational interviewing to boost self-efficacy, thereby establishing a virtuous cycle of “knowledge-resources-confidence”.